Pemikiran Pendidikan Islam Ibnu Rusyd dalam Bingkai Filsafat Rasional - Aidil Fitri; Diana; Mukhtar Zaini Dahlan; Hatta; Mar’atun Sholiha; Fatoni Achmad (Universitas Garut, 2026)
Contemporary Islamic education still faces an epistemological problem in the form of a dichotomy between religious knowledge and rational knowledge, which has resulted in a weak tradition of critical and integrative thinking among students. This condition demands an effort to reconstruct the paradigm of Islamic education that is able to integrate reason and revelation harmoniously. This study aims to analyze Ibn Rushd's Islamic educational thought within the framework of rational philosophy and its relevance to the development of contemporary Islamic education. This study uses a qualitative approach through document study with primary data sources in the form of Ibn Rushd's works and secondary sources in the form of books, journal articles, theses, and relevant proceedings. Data collection techniques were carried out through systematic literature searches, while data analysis uses content analysis methods to examine the educational concepts contained in Ibn Rushd's thought. The results of the study indicate that Ibn Rushd's concept of Islamic education is built on the foundation of integration between reason and revelation as two complementary sources of knowledge. Education is seen as a process of developing rational, spiritual, and moral potential in a balanced manner, with the aim of forming individuals who are knowledgeable, moral, and critical thinkers. In terms of curriculum, Ibn Rushd emphasized orientation toward religious goals, the formation of noble morals, and the strengthening of systematic and rational academic reasoning. Meanwhile, the educational methods he developed were based on a demonstrative approach (burhānī), dialogue, discussion, and the use of inductive and deductive methods. These findings confirm that Ibn Rushd's thinking has strategic relevance in formulating an integrative, rational, and contextual paradigm for Islamic education, in order to address the challenges of education in the modern era.